Follow Up of Newborns Exposed to Paclitaxel in Utero Evident by Metabolites in First Meconium Sample [28H]. (May 2020) - Cardonick, Elyce; Akoto, Serwaa; Doan, Mary; Xu, Peining J.; Snyder, Nathaniel; Broadrup, Robert
Abstract : INTRODUCTION: Paclitaxel is excluded from breast cancer treatment during pregnancy due to limited neonatal follow up. We confirmed fetal paclitaxel exposure by detection of chemotherapeutics in the first newborn meconium. Birth details and follow up of these newborns are reported. METHODS: Women receiving chemotherapy during pregnancy consented to submit their newborns' initial meconium. Liquid chromatography-high resolution mass spectrometry screened for chemotherapeutics, while blinded to maternal treatment. Medical record review and questionnaires completed by obstetricians and pediatricians provided newborn details. The institutional review board approved of this study. RESULTS: Mean gestational age (GA) at first taxane was 27.0 +/- 5.8 weeks, following anthracycline based treatment for breast cancer. Paclitaxel and metabolites were identified in meconium of all exposed newborns. Birthweight was less than ten percent in three infants. Three congenital anomalies: hip dysplasia (breech presentation); mitral valve stenosis; Cleidocranial Dysostosis. Mean age at follow up 13.2.5 + 5.5 months, ranges from 6 to 25 months. Pediatricians report treatment for eczema, recurrent otitis media, iron deficiency anemia and sinusitis. One child, not initially born with growth restriction is less than ten percent for height and weight at 15 months of age. However, all children are meeting developmental milestones. CONCLUSION: Detection of taxane or metabolites was not significantly related to GA at first taxane, GA at delivery, number of taxane cycles, birthweight, or days between last taxane and birth. Despite in utero fetal exposure to taxane, all are meeting milestones at a median age of 19 months.